POLA KONSUMTIF LIFE STUDENT CITY’S PEKANBARU PROVINCE OF RIAU - Khoirunnas "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted in the city of Pekanbaru province of Riau. The purposeof this research is To know how the consumption of the life of the student City’sPekanbaru. This study titled “Pola Konsumtif Life Student City’s Pekanbaruprovince of Riau”. The focus of this research is How the impact of the behavior ofkonsumtif students against the value of academic as well as the lecture bersistemactivities in the city of Pekanbaru. The writer just taking a sample of Researchtake as much as 5 people students. The writer use a technique Snowball Samplingin determine the respondents in the study. Students who studied is students whohave a tendency to make fun of as the purpose of life (hedonism), make acollection of personal as the primary (shopaholic) and the pattern of who knowsno bounds (seksualisme). The writer using the thedescriptive kualitatif.Instruments data is observations, the interview, and the documentation. Theresults of research suggests that In research conducted the researchers foundsome patterns behavior konsumtif students Riau University namely PolaKonsumtif Shopaholic (On this pattern student is an individual who is veryexcessive in the use of money, time and of them. Informants dreadfullyextravagant in shopping. Not only in belana, informant also involved in the ofyoung people who waste of time for the sake of personal pleasures. The patternKonsumtif Hedonisme (On this pattern the researchers found that the informantdeliberately looking for fun in continuous in order to eliminate the burden ofthem. Although problems facing the informant is not a problem that should be tooto think. Informants just want to fill in the days and time for fun.Keywords: Pola Konsumtif, Pola Konsumtif Life Student